RESISTANCE LEVEL STUDENTS STUDY CARDIORESPIRATORY PJKR STKIP PASUNDAN CIMAHI 2016/2017 ACADEMIC YEAR IS MEASURED USING THE BEEP TEST - Sobarna, Akhmad (Program Pascasarjana Universitas Negeri Jakarta, 2016)
This study aims to determine the level of cardiorespiratory endurance student study program PJKR STKIP Pasundan Cimahi Academic Year 2016/2017 were measured using beep test. The population in this study were all new students study program PJKR STKIP son Pasundan Cimahi Academic Year 2016/2017 which amounted to 392 people. Sampling technique used in this study is total sampling, sampling in this study as many as 329 new students study program PJKR STKIP Pasundan Cimahi Academic Year 2016/2017. The instrument used to measure cardiorespiratory endurance is a test Beep Test with the criteria of Davis, at.all (1992). Quantitative descriptive method is used as a method of research to find new students cardiorespiratory endurance. Data from the description indicates that the level of resistance cardiorespiratory for male students, 0% have categories Superior, 3% in the category of Very Good, 7% in the good category, 34% in the Average category, 18% in the category of less and 38% in the category Very Less. Seeing the results of research that has been presented, the need for improvement of cardiorespiratory endurance capability on the student study program PJKR.